2017
DOI: 10.1097/mao.0000000000001545
|View full text |Cite
|
Sign up to set email alerts
|

Selective Stimulation of Facial Muscles Following Chronic Intraneural Electrode Array Implantation and Facial Nerve Injury in the Feline Model

Abstract: Background Our group has previously shown that activation of specific facial nerve (FN) fiber populations and selective contraction of facial musculature can be achieved through acute intraneural multi-channel microelectrode array (MEA) implantation in the feline model. Hypothesis Selective stimulation of facial muscles will be maintained in the setting of (1) chronic and (2) acute MEA implantation following FN injury and subsequent recovery. Methods This study included seven cats. In three cats with norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…This may have been due to variations in the study environment, including EMG electrode placement, prior stimulations, and level of animal sedation. Nevertheless, the effective selectivity of the MCE, as demonstrated in this and previous works [ 20 , 23 , 24 ], is encouraging for future investigations and an eventual human implantation trial.…”
Section: Discussionsupporting
confidence: 67%
“…This may have been due to variations in the study environment, including EMG electrode placement, prior stimulations, and level of animal sedation. Nevertheless, the effective selectivity of the MCE, as demonstrated in this and previous works [ 20 , 23 , 24 ], is encouraging for future investigations and an eventual human implantation trial.…”
Section: Discussionsupporting
confidence: 67%
“…Increases in stimulation current levels resulted in corresponding increases in EMG voltage response. Moreover, long-term presence of the microelectrode array in the facial nerve confirmed the efficacy and stability of this intraneural stimulation approach [131]. Intraneural stimulation of restricted neural populations with one or more multichannel arrays may play a role in reanimating the face for patients with permanent facial paralysis and may also help rehabilitate other motor and sensory functions throughout the central and peripheral nervous systems [129].…”
Section: Penetrating Multi-channel Arraysmentioning
confidence: 85%
“…Previous work has demonstrated the utility of a penetrating microelectrode array (MEA), when inserted into the FN, to stimulate movement and contraction in specific muscles in a feline model. 9,10,13 However, the histological reaction and electrode migration that ensued following chronic implantation warranted the investigation of alternative electrodes that would mitigate the fibrotic response and have enhanced stimulation characteristics when chronically implanted. These results have led to the exploration of the ability of a MCE to selectively activate facial muscles.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Previous works have suggested that neuroprosthetic technologies may be efficacious in the treatment of FP in animal models. [9][10][11] Functional restoration of paretic or paralyzed FN activity (in the case of intact and still functional FN and distal musculature) requires selective stimulation of the fascicle, which then subsequently activates specific muscles. Here, we test the ability of a multichannel cuff electrode (MCE) to selectively activate feline facial muscles in both acute and chronic settings, and in both uninjured and injured FN.…”
Section: Introductionmentioning
confidence: 99%